The Growth and Development of Black Theatre in Canada: A Starting Point - Breon, Robin (Theatre Research in Canada / Recherches théâtrales au Canada, 1988)
Black theatre in Canada has a presence dating back to 1849 and perhaps further. The profile of organizations and personalities detailed in this article shows the growth of this movement since the mid-nineteenth century, as well as problems and obstacles encountered by visible minorities in their struggle to enter the mainstream of Canadian cultural life. La contribution des Noirs au théâtre canadien remonte à 1849, et peut-être même plus loin. Ce survol des organismes et des individus qui contribuèrent à ce théâtre dépeint son évolution depuis le milieu du XIXe siècle, tout en soulignant les problèmes et les obstacles qu’encontrèrent les minorités ’visibles’ dans leur lutte pour appartenir à une commune culture canadienne.